Julia Biggane / John Macklin (eds.): A Companion to Miguel de Unamuno. Woodbridge: Tamesis 2016 (Colección Támesis / A, 360). 243 páginas - Sánchez Jiménez, Antonio (My University, 2017)
Review of Biggane and Macklin's Companion to Miguel de Unamuno
Keywords: Miguel de Unamuno